PENGEMBANGAN DESTINASI WISATA PADA CURUG CINULANG, KABUPATEN SUMEDANG DENGAN PENDEKATAN ANALISIS SWOT - Dewanta Fachrureza (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2020)
Tourist visits to Sumedang from year to year have grown quite rapidly. However, it cannot be denied that there is still an imbalance in tourist visits between districts, which is quite striking because the quality of tourist destinations between districts in West Java is not evenly distributed. This study tries to explore concepts in the development of nature-based destinations in the Curug Cinulang area, which are studied using a SWOT approach. The results of the analysis refer to the strategy to improve weaknesses to take the opportunities that exist in the tourist location (WO). Applications in the development of tourist sites that aim to improve several variables, including: redesign of access to tourist sites, Development of tourism facilities and accessibility; The development focuses on matters of natural charm and also includes flora culture as well as tourist attractions which will be included in the beautiful, unique and authentic category by using scenery or landscapes as the first impression and tourist icon of Curug Cinulang, initial procurement of the most basic facilities such as parking, sign referrals, public seating, gazebos, toilets, parking and so on, and the development of iconic or instagramable attractions to maximize visits from millennials. Keyword ; Strength, Weakness, Opportunity, Destination development, Tourist attraction